Effects of Freeze Vacuum Drying Combined with Hot Air Drying on the Sensory Quality, Active Components, Moisture Mobility, Odors, and Microstructure of Kiwifruits - Lihui Zhang; Yu Qiao; Chao Wang; Li Liao; Lu Liu; Defang Shi; Kejing An; Jianzhong Hu; Qing Xu (Journal of Food Quality)
In this study, freeze vacuum drying (FVD), hot air drying (AD), and FVD combined with AD (FVD-AD) were used to dry kiwifruits. Dried products were analyzed comprehensively on their sensory quality, active components, moisture mobility, odors, and microstructure. Results showed that the FVD-AD saved time by 38.22% compared with FVD while maintaining an acceptable product quality. The antioxidant properties of FVD-AD were lower than those of FVD but significantly higher than those of AD. Moreover, compared with FVD products, FVD-AD products were moderately hard (5252.71 ± 33.53 g) and improved in color, bound water, and microstructure. Additionally, FVD-AD consumed lesser drying time and energy than FD. According to cluster analysis, the odors of FVD-AD products were similar to those of the fresh ones. Principal component analysis of physicochemical and drying cost indicated that FVD-AD was a promising processing technique for functional kiwifruit snacks.